Postnatal development of bacterial population in the gastrointestinal tract of calves - Lukás, F; Koppová, I; Kudrna, V; Kopecný, J (Folia microbiologica, 2007)
Bacterial 16S rDNA from fecal samples of two calves were amplified by PCR and analyzed by denaturing gradient gel electrophoresis; selected bands were sequenced. Escherichia coli and Bifidobacterium animalis were the initial colonizers, followed by species closely related to the genera Bacteroides, Clostridium and Faecalibacterium. Change of diet was connected with shifts of bacterial population and with the occurrence of many bacterial species that have not been cultured up to now. The diet change corresponded with an alteration in a volatile-fatty-acid concentration in fecal samples.
Keywords: DNA bakterií; feces; DNA, Ribosomal; Electrophoresis; Sequence Analysis, DNA; Ecosystem; novorozená zvířata; RNA ribozomální 16S; Escherichia coli; zvířata; RNA, Ribosomal, 16S; Feces; elektroforéza; sekvenční analýza DNA; Animals, Newborn; DNA, Bacterial; Cattle; polymerázová řetězová reakce; skot; Polymerase Chain Reaction; ribozomální DNA; Bacteria; Animals; Bifidobacterium; Gastrointestinal Tract; gastrointestinální trakt; ekosystém